The Standard of Living in the Soviet Union, 1928-1949. - Allen, R (University of British Columbia, 1997)
New estimates for the growth in aggregate consumption in the Soviet Union from 1929 to 1940 are developed. While Bergson's The Real National Income of Soviet Russia since 1928 had suggested a decline in per capita consumption, this paper argues that consumption rose sognificantly. The paper includes a detaild discussion of Bergson's procedures.